Meta-analysis of hybrid immunity to mitigate the risk of Omicron variant reinfection - Zheng, Huiling; Wu, Shenggen; Chen, Wu; Cai, Shaojian; Zhan, Meirong; Chen, Cailin; Lin, Jiawei; Xie, Zhonghang; Ou, Jianming; Ye, Wenjing (Frontiers in Public Health, 2024)
Background: Hybrid immunity (a combination of natural and vaccine-induced immunity) provides additional immune protection against COVID-19 reinfection. This meta-analysis aims to explore hybrid immunity to mitigate the risk of Omicron variant reinfection and its protective durability to provide a new evidence-based basis for the development and optimization of immunization strategies and improve the public's awareness and participation in COVID-19 vaccination, especially in vulnerable and at-risk populations.Methods: Embase, PubMed, Web of Science, Chinese National Knowledge Infrastructure, and Wanfang databases were searched for publicly available literature up to 10 June 2024. The Newcastle-Ottawa Scale assessed the risk of bias in included cohort and case-control studies, while criteria recommended by the Agency for Health Care Research and Quality (AHRQ) evaluated cross-sectional studies. The outcome was Omicron variant reinfection, reported as an Odds Ratio (OR) with its 95% confidence interval (CI) and Protective Effectiveness (PE) with 95% CI. The data were pooled using a random-or fixed-effects model based on the I 2 test. The PROSPERO registration ID is CRD42024539682.Results: A total of 33 articles were included. Compared with the natural immunity group, the hybrid immunity (booster vaccination) group had the highest level of mitigation in the risk of reinfection (OR=0.43, 95% CI:0.34-0.56), followed by the complete vaccination group (OR=0.58, 95% CI:0.45-0.74). Compared with the complete vaccination-only group, the hybrid immunity (complete vaccination) group mitigated the risk of reinfection by 65% (OR=0.35, 95% CI:0.27-0.46), and the hybrid immunity (booster vaccination) group mitigated the risk of reinfection by an additional 29% (OR=0.71, 95% CI:0.61-0.84) compared with the hybrid immunity (complete vaccination) group. The effectiveness of hybrid immunity (incomplete vaccination) in mitigating the risk of reinfection was 37.88% (95% CI: 28.88%-46.89%) within 270-364 days; whereas, the effectiveness after complete vaccination was 54.36% (95% CI: 50.82%-57.90%) within 270-364 days, and the effectiveness of booster vaccination was 73.49% (95% CI: 68.95%-78.04%) within 90-119 days.Conclusions: Hybrid immunity was significantly more protective than natural or vaccinationinduced immunity, and booster doses were associated with enhanced protection against Omicron. Although its protective effects waned over time, vaccination remains a crucial measure for controlling COVID-19.